Cost effectiveness of a 1-hour high-sensitivity troponin-T protocol: An analysis of the RAPID-TnT trial. (February 2022) - Chuang, Ming-yu Anthony; Gnanamanickam, Emmanuel S.; Karnon, Jonathan; Lambrakis, Kristina; Horsfall, Matthew; Blyth, Andrew; Seshadri, Anil; Nguyen, Mau T.; Briffa, Tom; Cullen, Louise A.; Quinn, Stephen; French, John K.; et al.
Highlights: This is the first randomised evaluation of the cost-effectiveness of a 0/1-hour high-sensitivity troponin protocol and has implications on clinical practice on a health system level. The results demonstrate that the 0/1-hour hs-cTnT protocol is safe and does not incur excess resource compared to the conventional 0/3-hour protocol. Whilst this cost-effectiveness analysis demonstrates superior ED efficiency and equivalent safety and resource associated with the 0/1-hour hs-cTnT protocol, further refinements in subsequent management is necessary to facilitate large-scale adaptation. Abstract: Background: To understand the economic impact of an accelerated 0/1-hour high-sensitivity troponin-T (hs-cTnT) protocol. Objective: To conduct a patient-level economic analysis of the RAPID-TnT randomised trial in patients presenting with suspected acute coronary syndrome (ACS). Methods: An economic evaluation was conducted with 3265 patients randomised to either the 0/1-hour hs-cTnT protocol (n = 1634) or the conventional 0/3-hour standard-of-care protocol (n = 1631) with costs reported in Australian dollars. The primary clinical outcome was all-cause mortality or new/recurrent myocardial infarction. Results: Over 12-months, mean per patient costs were numerically higher in the 0/1-hour arm compared to the conventional 0/3-hour arm (by 472.49/patient, 95% confidence interval [95 %CI]: -1, 380.15 to 2, 325.13, P = 0.617) with no statistically significant difference in primary outcome (0/1-hour: 62/1634 [3.8%], 0/3-hour: 82/1631 [5.0%], HR: 1.32 [95 %CI: 0.95–1.83], P = 0.100). The mean emergency department (ED) length of stay (LOS) was significantly lower in the 0/1-hour arm (by 0.62 h/patient, 95 %CI: 0.85 to 0.39, P < 0.001), but the subsequent 12-month unplanned inpatient costs was numerically higher (by 891.22/patient, 95 %CI: -96.07 to 1, 878.50, P = 0.077). Restricting the analysis to patients with hs-cTnT concentrations ≤ 29 ng/L, mean per patient cost remained numerically higher in the 0/1-hour arm (by 152.44/patient, 95 %CI:-1, 793.11 to 2, 097.99, P = 0.988), whilst the reduction in ED LOS was more pronounced (by 0.70 h/patient, 95 %CI: 0.45–0.95, P < 0.001). Conclusions: There were no differences in resource utilization between the 0/1-hour hs-cTnT protocol versus the conventional 0/3-hour protocol for the assessment of suspected ACS, despite improved initial ED efficiency. Further refinements in strategies to improve clinical outcomes and subsequent management efficiency are needed.